Elevation of serum creatine kinase during methimazole treatment of Graves disease in a 13-year-old girl and a literature review of similar cases - Hyeseon Kim; Jinsup Kim; Rimm Huh; Sung Yoon Cho; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2015)
We report a 13-year-old girl with Graves disease, who showed an increased level of serum creatine kinase (CK) accompanied by myalgia after methimazole (MMI) treatment. This patient developed muscular pain two weeks after MMI administration, along with increased CK levels. The level of thyroid hormone was within the normal range when she showed increased CK levels. After the MMI dose was decreased and levo-thyroxine was added, serum CK levels decreased to normal and the myalgia improved. The pathophysiologic mechanism of this effect has not yet been elucidated. An acute relatively hypothyroid state occurs secondary to antithyroid drug (ATD) administration in chronic hyperthyroidism, which may cause changes in the CK levels. In this report, we present a rare pediatric case, along with a literature review of similar cases. In the initial state of MMI treatment, myalgia should be detected and when it occurs, CK levels should be measured. The clinical strategy of monitoring CK levels with the aim of normalizing thyroid hormones is helpful in case of the development of adverse reactions, such as myalgia, during ATD treatment for Graves disease in children.